The influence of regulation, planning and controlling on financial management performance through competence as an intervening variable in Regional Apparatus Organizations in the district of Karimun - Sari, Pri Handani Bayu; Rumengan, Angelina E.; Indrawan, Mohamad Gita (Global Academy of Business Studies, 2025)
Purpose: This study aims to provide empirical evidence of the effects of regulation, planning, and control on financial management performance, with competency serving as a mediator. Research Methodology: The population of this study was 122 Financial Management Employees in the OPD Mandatory Basic Services of Karimun Regency, and all population elements were used as respondents using the census sampling technique. The data analysis method used was SEM-PLS with Smart-PLS software version 3.0. Results: Regulation and control had a positive but insignificant impact on financial management performance, whereas they significantly affected competence. Planning positively and significantly influenced both financial management performance and financial competence. Competence mediated the effect of planning on performance but did not mediate the impact of regulation and control. Conclusions: Although regulation and control positively influence competence, they do not directly affect financial management performance. Planning significantly enhances both performance and competence, with competence mediating the impact of planning. Limitations: The study is limited to the financial management employees of Karimun Regency; therefore, its findings may not be generalizable to other regions. Second, the study utilized cross-sectional data, which restricts causal inferences. Contribution: This study deepens the understanding of how regulation, planning, and control impact financial management performance and highlights the mediating role of competence in government organizations’ financial management performance.